Functions and wν-Lindelöf with respect to a hereditary class - Abuage, Mariam M.; Kilicman, Adem (Taylor & Francis, 2018)
A collection of a nonempty subsets of is called hereditary class if it is closed under hereditary property. In this work, we define and study the notion of some generalizations of -Lindelöf generalized topological spaces with respect to a hereditary class, namely; -Lindelöf hereditary generalized topological spaces. Moreover, investigate basic properties of the concepts, its relation to known concepts and its preservation by functions properties.